2003
DOI: 10.1046/j.1365-2036.2003.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in relation to symptoms in patients with gastro‐oesophageal reflux disease — an analysis based on the ProGERD initiative

Abstract: SUMMARYAims: To determine the impact of gastro-oesophageal reflux disease (GERD) on the quality of life, to assess changes in the quality of life during treatment with esomeprazole and to define factors that can predict these changes. Methods: Patients with GERD (n ¼ 6215) were included in a prospective cohort study (ProGERD). All patients underwent endoscopy and received esomeprazole. At baseline and after 2 weeks of treatment, symptoms and quality of life were assessed. Factors that influenced changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
201
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(226 citation statements)
references
References 36 publications
14
201
0
11
Order By: Relevance
“…12,14,15 Although HRQoL improves with treatment, persistent symptoms after PPI therapy are associated with a reduced HRQoL. 14,16,17 However it is unclear how the recurrence of GERD symptoms impacts patients' HRQoL. Furthermore, there have been no reports regarding the difference in the impact of relapsed GERD symptoms on HRQoL between patients with erosive reflux disease (ERD) and non-erosive reflux disease (NERD).…”
Section: Introductionmentioning
confidence: 99%
“…12,14,15 Although HRQoL improves with treatment, persistent symptoms after PPI therapy are associated with a reduced HRQoL. 14,16,17 However it is unclear how the recurrence of GERD symptoms impacts patients' HRQoL. Furthermore, there have been no reports regarding the difference in the impact of relapsed GERD symptoms on HRQoL between patients with erosive reflux disease (ERD) and non-erosive reflux disease (NERD).…”
Section: Introductionmentioning
confidence: 99%
“…5 As a group, patients with NERD have symptom and quality of life scores similar to patients with erosive reflux disease (ERD). 4,6 Patients can progress from NERD to ERD, even on proton-pump inhibitor (PPI) therapy, but progression from ERD to BE is uncommon and from NERD to BE is very uncommon. [7][8][9] Labenz et al reported on the progression of GERD (ProGERD) study of 3,894 patients with GERD who underwent baseline endoscopy and repeat endoscopy at 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…Therapy with proton pump inhibitors (PPI) was reflected by an increase in psychological and physical status measured with SF-36. Among others, the improvement was more evident in patients with more severe oesophagi-tis (C and D according to the Los Angeles scale) as well as in those with more severe manifestations [13]. The level of quality of life in reflux disease was comparable to that observed in mild-degree heart failure [18].…”
Section: Quality Of Life In Patients With Gastroesophageal Reflux Dismentioning
confidence: 87%
“…Although GERD is a mild condition, HRQOL in GERD patients is significantly lower than in the general population [12][13][14]. Revicki et al [12] observed that GERD impairs HRQOL in all areas of health analysed with the SF-36 questionnaire.…”
Section: Quality Of Life In Patients With Gastroesophageal Reflux Dismentioning
confidence: 99%